Risk Factors for Soil-Transmitted Helminthiasis in Preschool Children Living in Farmland, North Sumatera, Indonesia - Sri Novianty; Yazid Dimyati; Syahril Pasaribu; Ayodhia Pitaloka Pasaribu (Journal of Tropical Medicine)
Background. Disease burden from soil-transmitted helminthiasis (STH) is mainly attributed to its chronic and insidious impact on health and quality of life. Strategy recommended by World Health Organization (WHO) to control it was previously focused on school-aged children, but now preschool-aged children are involved. This study was intended to determine STH infection risk factors in preschool children. Methods. A cross-sectional study was conducted in Suka Village, North Sumatera, Indonesia, from October to December 2016. Subjects were children aged 1 to 5 years without history of taking antihelminthic. Subjects were obtained by consecutive sampling. Demographic data and risk factors for helminthiasis were collected using questionnaire-based interview. Subjects were divided into two groups, positive and negative STH infection, based on Kato Katz method. Analysis was done using chi-square and logistic regression test. p value < 0.05 was considered significant. Results. We enrolled 90 subjects in this study, with the mean age being 31.7 months. STH infection prevalence was 34.4%. Statistical analysis revealed that mother/caregiver hand washing habit (p=0.007), mother/caregiver nail trimming habit (p=0.018), and children nail trimming habit (p=0.022) were significant risk factors for STH infection. Conclusion. Mother/caregiver hand washing habit is the most influential risk factor for STH infection in preschool children.